Penerapan Metode Perbandingan Eksponensial untuk Pemilihan Pengajuan Pembiayaan Pada KSPPS BMT NU Sejahtera Gemolong - Widyasari Widyasari; Sri Hariyati Fitriasih; Tri Irawati (Jurnal Ilmiah SINUS, 2022)
One of the institutions that provides financial services is a cooperative. Savings and loans cooperatives under Islam law (Shariah) provide financing to its members who apply for loan. However, the selection of these members is still using the manual method. This allows members who apply for financing to experience bad credit and its selection takes a long time. The purpose of this study is to create a decision support system for selecting a financing application so that bad credit does not occur. Algorithm method in this study was Exponential Comparison Method. Its system implementation used Visual Studio programming language with SQL Server database. As a result, there is an application for a decision support system of financing that can be used for making decisions about the eligibility of members in financing. This application had been tested by using Blackbox. The result of this system had features to cultivate data, count the eligible members, show the results of decision based on the total value. Its reports consisted of members’ identity, members’ criteria, and financing feasibility reports. The value total of exponential comparison from customer candidates with range and value of 75 obtained the financing. Meanwhile, range and value of 50-75 was reconsideration and 50 was not eligible to receive the financing. The alternative data of 10 financed prospective members reached 50% in this result of study. Testing was done by comparing the results of manual calculations and the results of system calculations.